Developing code of ethics in midwifery counseling: A modified Delphi study - Vafa Senobar; Ehsan Shamsi Gooshki; Tahmineh Farajkhoda; Zahra Mehdizadeh Tourzani; Razieh Lotfi (Tehran University of Medical Sciences, 2023)
Background & Aim: The interdisciplinary nature of the profession of counseling in midwifery underscores the need for the establishment of an ethical framework to guide the provision of counseling services in various areas of midwifery and women's health. Consequently, the present study has been conducted with the objective of formulating code of ethics in midwifery counseling. Methods & Materials: The present study is a developmental study using the Delphi method, which was conducted in three stages in 2020. The first stage involved qualitative content analysis to review the texts, and the development of an initial draft of ethical codes. In the second stage, expert opinions were sought from professionals specializing in medical and midwifery ethics to evaluate and make revisions to the initial draft. The third stage involved validation of the draft codes and their finalization. Results: According to the results of the qualitative content analysis, a total of 182 codes were obtained from the texts and classified into eight categories. However, through the Delphi rounds, the number of categories was subsequently reduced to six, resulting in a decrease in the number of codes to 121. The identified categories included; "Professional competence", "Professional communication", "Management of client data", "Ethical considerations in tele-counseling", "Ethical considerations in midwifery counseling education", and "Ethical considerations in research". These categories were established with a consensus level of 92.4%. Conclusion: In this research, a set of ethical codes was obtained from the experts' opinions in relevant disciplines from various universities across the country, with appropriate validity and consensus levels. These codes can be used in providing counseling services in midwifery, promoting safety and adhering to ethical principles and values.